NEURO-MEMORY RESPONSE TO PHYSICO-CHEMICAL CONDITIONS OF WATER QUALITY IN THE BIOMONITOR GAMBUSIA PUNCTATA, POEY 1854 - Argota-Pérez, George (2021)
The aim of the study to evaluate the memory neuro-response to physical-chemical conditions of waterquality in the biomonitor Gambusia punctata, Poey 1854. The study was carried out between Februaryand April 2021 in the environmental zone of approach that corresponds to the lower part of theAlmendares river, Havana, Cuba. The physicochemical parameters (PFQ) were measured in situ: dissolved oxygen, pH, total dissolved solids and electrical conductivity. An experiment was carried outthat consisted of introducing a rod every two hours during a range of eight hours where a simulated larva of Aedes aegypti (Linnaeus, 1762) was transported from its interior, and then the neuro-memory of time was recorded for the reaction towards its probable consumption. The brains of the males were measured against the quality of the water. The PFQs did not meet the recommended values. The reaction time towards the orientation of the stimulus decreased as the hours passed and there were no statistically significant differences, indicating immediate neuro-memory. There were also no significant differences in brain growth. It is concluded that as time passes there is a reaction to a recognized stimulus during the life cycle and, probably, the delay is due to environmental conditions. However, when the stimulus is presented, the reaction time is immediate; therefore, there is neuroimaging towards information learned and related to food, such as the larvae of A. aegypti.